2018
DOI: 10.1007/s11069-018-3287-y
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling effects of an asphalt road at a dike crest on dike cover erosion onset during wave overtopping

Abstract: Structures integrated in a grass-covered dike may increase erosion development. Currently, safety assessment methods for flood defences are only applicable for a conventional grass-covered dike and the effects of structures on dike cover erosion are poorly understood. Since many dikes have a road on top, it is important to study the effect of such a road structure on erosion onset during wave overtopping. To investigate this effect, a coupled hydrodynamic-erosion model was developed. The erosion onset caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(89 citation statements)
references
References 16 publications
3
86
0
Order By: Relevance
“…While the erosion is generated by one single wave, it has been observed that failure of the dike cover is mostly achieved by the overtopping of numerous waves during a storm event [12]. The time span in which erosion caused by a single wave takes place at a specific location is in the order of seconds [26] and it is termed total wave overtopping time (…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…While the erosion is generated by one single wave, it has been observed that failure of the dike cover is mostly achieved by the overtopping of numerous waves during a storm event [12]. The time span in which erosion caused by a single wave takes place at a specific location is in the order of seconds [26] and it is termed total wave overtopping time (…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The first CFD model (RCD), originally built in Ref. [26,35], was based on the scanned profile obtained as a final condition after the 0.01 m 3 /s/m experiment (q10_sc2: where q implies the mean overtopping discharge in l/s/m and sc2 refers to scan 2, the first profile scan after the q10 event, see Table 1). This profile includes an asphalt road of 3.1 m width with adjacent eroded transition gaps on each side of approximately 0.5 m each ( Figure 4).…”
Section: Cfd Modelsmentioning
confidence: 99%
See 3 more Smart Citations